2020
DOI: 10.1039/d0nr03056b
|View full text |Cite
|
Sign up to set email alerts
|

Flexible piezoelectric energy harvester with an ultrahigh transduction coefficient by the interconnected skeleton design strategy

Abstract: The freeze-casted 2-2 type piezocomposite has an ultrahigh transduction coefficient of 58 213 × 10−15 m2 N−1, which is significantly better than those of previously reported composite materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
0
21
0
Order By: Relevance
“…98 showed that this structure had a high Young's modulus compared to pure PDMS and 0-3 type PZN-PZT/PDMS composite due to the existence of the interconnected skeleton structure that greatly improves stress transfer. 138 Therefore, porous ceramic-based ferroelectric composites with aligned structure can exhibit improved mechanical properties.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…98 showed that this structure had a high Young's modulus compared to pure PDMS and 0-3 type PZN-PZT/PDMS composite due to the existence of the interconnected skeleton structure that greatly improves stress transfer. 138 Therefore, porous ceramic-based ferroelectric composites with aligned structure can exhibit improved mechanical properties.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The flexible nature of the polymer‐based energy harvester makes it suitable for the appropriate technique for providing power to the flexible wearing electronic devices. [ 3 ] The simple production technique or cost‐effective method is highly required to reduce the overall cost of the flexible energy harvester. [ 4 ] Because of some of the electronic instruments depend on wireless operations, the use of flexible energy harvester is one of the essential techniques.…”
Section: Introductionmentioning
confidence: 99%
“…There is only a little enhancement of the V OC of the BCTZ/0.04Ag PEH compared to that of the BCTZ PEH, while the I SC of BCTZ/0.04Ag PEH significantly increases to 100 μA (peak–peak), which is 25% higher than that of BCTZ PEH (79 μA). As shown in Figure c and Table , the obtained power generation performance in BCTZ/0.04Ag PEH is much higher than that of other widely reported PEHs made of flexible and bulk piezoelectric materials. ,,,,, Figure d shows the charging curve of the BCTZ and BCTZ/0.04Ag PEHs charging an electrolytic capacitor (22 μF, 25 V) under continuous vibration conditions (91 Hz and 1 g). While charging for 25 s, the capacitor was charged to a voltage of 6 V using the BCTZ PEH as a power supply; however, a much larger voltage of 10 V can be reached using the BCTZ/0.04Ag PEH as a power supply benefiting from the large current performance.…”
Section: Resultsmentioning
confidence: 88%